Experimental and Theoretical Investigation of the Elastic Properties of Zinc oxide - MUHAMMAD YAMEEN (International Journal of Scientific Research and Innovative Studies, 2022)
The main aim of this study is to review and compile the elastic properties of zinc oxide and investigate which density functional method either the LDA or the GGA method have excellent agreement with the experimental data. The LDA values and the GGA values of elastic stiffness constant Cij(GPa) and poisson’s ratio of zno are analyzed statistically and compared with the surface ultrasonic , brillouin zone and acoustic technique experimental values. Similarly, the LDA and GGA values of Bulk modulus and Young’s modulus (GPa) are statistically analyzed and compared with the experimental values. Moreover, it was found that that the LDA values of stiffness constant exhibited maximum deviation 17.8%,15.84%,14.2% from the ultrasonic, brillouin and acoustic values, whereas, the GGA indicated 27.6%,29.67%,2.7% maximum deviation from the ultrasonic, brillouin and acoustic experimental values respectively. The Poisson’s ratio LDA values are exhibited deviation 32.7%,16.1%,2.1% while the GGA values exhibited 51.3%,28%,0.24% from the ultrasonic, brillouin zone and acoustic experimental values separately. The bulk modulus and young modulus LDA values exhibited deviation 2.6% and 10% while GGA values exhibited 6.4% and 33% from the experimental values. As a result, it is revealed that the LDA method has good agreement than the GGA.